“This is a business….. It’s not a one-to-one” Exploring early years educators’ psychological and financial well-being in non-profit and for-profit early years settings in Ireland - Sharkey, Elaine (Marino Institute of Education, 2020)
This research study focuses on comparing early years educators’ psychological and financial well-being in community, private independent and private chain settings in Ireland. Drawing particularly on self-determination theory and Bronfenbrenner’s (1979) ecological systems theory, this study focuses on exploring the psychological needs of autonomy, competency and relatedness. This research study applied a mixed-methods sequential explanatory design, where findings from the questionnaire (n=115) were used to inform the structure of the semi-structured interviews (n=4). Findings from this study indicate that the relationship educators have with children in their setting is of particular importance and one that drives their intrinsic motivation to remain in their settings. However, it is also clear that there are numerous issues affecting their ability in ensuring the formation of consistent and meaningful relationships. Findings also suggest that educators who have informal relationships with management have greater job satisfaction, provide higher quality of care and education and feel more valued by management. This research also revealed differences in educator well-being among the sub-groups, with educators from community settings experiencing better working conditions and higher job-satisfaction than educators in private settings. There were significant variances however, between independent private and private chain settings, suggesting that the problem may not lie in the ‘for-profit’ status, but in the prioritising of profit. A concerning finding from the study found that the majority of educators across all the sub-groups described dissatisfaction with their pay, felt a lack of recognition from both the government and society and more than half expressed a strong desire to permanently leave the sector. It is recommended that policy considers the benefits of a holistic working environment for educators, through prioritising time for relationships, encouraging competence and promoting autonomy.